Lessons from Jan Amos Comenius for Pentecostals and Charismatics - Hittenberger, Jeffrey S. (Pneuma, 2026)
Jan Amos Comenius (1592-1670) was a church leader and educational philosopher in early modern Europe who, because of his pedagogical innovation, has come to be known as "the Father of Modern Education." Comenius led the Unitas Fratrum (translated Unity of the Brethren and also known as the Czech Brethren) through decades of suffering and exile and planted the seeds for what would come to be known as the "Moravian Pentecost" of 1727. This article explores the contributions of Comenius and the lessons contemporary Pentecostals and Charismatics can learn from his life, spirituality, and writings about integrating a passion for God with a passion for learning, mission, and redemptive service.